KEPADATAN POPULASI PREDATOR, PESAING, DAN SIMBION KUTUDAUN PADA TANAMAN KACANG PANJANG PASCAAPLIKASI INSEKTISIDA - Nur Yasin, Listianingsih, Lestari Wibowo, dan F. X. Susilo . (Universitas Lampung, 2004)
The population density of Aphis sp., their predators, competitors, and symbionts in longbean field treated with insecticide. This study was aimed to determine the effect of profenofos insecticide application on 1) the population density of Aphis sp., their predators (coccinellids and syrphids), competitor (Empoasca sp.) and symbionts (ants), and 2) the interactions between the aphid and the predator, the aphid and the symbiont, and the aphid and the competitor in the longbean field. The experiment was arranged in completely randomized design with three levels of profenofos treatments (P1= profenofos sprayed weekly, P2= profenofos sprayed biweekly, and K= unsprayed). Each treatment was replicated six times. Population density (insect number/longbean hill) was observed three times a week, totaling 16 observations during the growing season. The result showed that profenofos spray decreased the population density of Aphis sp. Profenofos treatment also suppressed coccinellid, syrphid, Empoasca sp., and ant population. However, the insecticide did not affect the correlation either between Aphis sp. and ant, between Aphis sp. and Empoasca sp., between ant and Empoasca sp., between ant and coccinellids/syrphids, or between Empoasca sp. and coccinellids/syrphids. It was clear from this study that profenofos strengthened the interaction between Aphis sp. and coccinellids. Aphis sp.—syrphid interaction was weekened by biweekly spray of profenofos, but was replenished by weekly spray of the insecticide.